Pengaruh - Yosia, Aldo; Argenti, Gili; Marsingga, Prilla (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research analyzes the influence and policies issued by Donald Trump that make conflicts appear more and more. The policies issued by Donald Trump have an impact on the Israeli-Palestinian conflict. With the superiority and support of the United States towards Israel, Palestine seems to be an 'enemy' and Israel as a 'friend' so this policy only becomes an obstacle to the peace process of the Israeli-Palestinian conflict. Because the United States is a superpower its foreign policy greatly influences international decisions, therefore various criticisms have not only been made by Palestine, but Donald Trump's actions have also drawn hot criticism from Middle Eastern countries and also countries in the world.